Genomic Analysis of Two Phylogenetically Distinct Nitrospira Species Reveals Their Genomic Plasticity and Functional Diversity - Ushiki, Norisuke (Front Microbiol, 2018)
The genus Nitrospira represents a dominant group of nitrite-oxidizing bacteria in natural and engineered ecosystems. This genus is phylogenetically divided into six lineages, for which vast phylogenetic and functional diversity has been revealed by recent molecular ecophysiological analyses. However, the genetic basis underlying these phenotypic differences remains largely unknown because of the lack of genome sequences representing their diversity. To gain a more comprehensive understanding of Nitrospira, we performed genomic comparisons between two Nitrospira strains (ND1 and NJ1 belonging to lineages I and II, respectively) previously isolated from activated sludge. In addition, the genomes of these strains were systematically compared with previously reported six Nitrospira genomes to reveal their similarity and presence/absence of several functional genes/operons. Comparisons of Nitrospira genomes indicated that their genomic diversity reflects phenotypic differences and versatile nitrogen metabolisms. Although most genes involved in key metabolic pathways were conserved between strains ND1 and NJ1, assimilatory nitrite reduction pathways of the two Nitrospira strains were different. In addition, the genomes of both strains contain a phylogenetically different urease locus and we confirmed their ureolytic activity. During gene annotation of strain NJ1, we found a gene cluster encoding a quorum-sensing system. From the enriched supernatant of strain NJ1, we successfully identified seven types of acyl-homoserine lactones with a range of C10–C14. In addition, the genome of strain NJ1 lacks genes relevant to flagella and the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas (CRISPR-associated genes) systems, whereas most nitrifying bacteria including strain ND1 possess these genomic elements. These findings enhance our understanding of genomic plasticity and functional diversity among members of the genus Nitrospira.